2019
DOI: 10.1007/s40262-019-00777-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Models for Prediction of Complex CYP2C8 and OATP1B1 (SLCO1B1) Drug–Drug–Gene Interactions: A Modeling Network of Gemfibrozil, Repaglinide, Pioglitazone, Rifampicin, Clarithromycin and Itraconazole

Abstract: BackgroundDrug–drug interactions (DDIs) and drug–gene interactions (DGIs) pose a serious health risk that can be avoided by dose adaptation. These interactions are investigated in strictly controlled setups, quantifying the effect of one perpetrator drug or polymorphism at a time, but in real life patients frequently take more than two medications and are very heterogenous regarding their genetic background.ObjectivesThe first objective of this study was to provide whole-body physiologically based pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…If this inductive effect of RIF is also absent in humans, it would help us gain mechanistic insight for complex DDIs involving OATP1B and enzyme. In previous reports no clear cut induction of OATP1B with respect to activity, mRNA or protein but an increase in OATP1B activity was assumed in the RIF-treated subjects (Lutz et al, 2018, Turk et al, 2019, raising the question of linkages between CYP3A, OATP1B, P-gp, BCRP, and MRP2 expression in humans and nonhuman primate species. By measuring the plasma RIF concentration, we have clearly shown that RIF stimulates its own clearance via induction of the metabolic enzyme (and transporter).…”
Section: Effects Of Rif On Oatp1b1 Gene Expression In the Liver Smalmentioning
confidence: 94%
See 1 more Smart Citation
“…If this inductive effect of RIF is also absent in humans, it would help us gain mechanistic insight for complex DDIs involving OATP1B and enzyme. In previous reports no clear cut induction of OATP1B with respect to activity, mRNA or protein but an increase in OATP1B activity was assumed in the RIF-treated subjects (Lutz et al, 2018, Turk et al, 2019, raising the question of linkages between CYP3A, OATP1B, P-gp, BCRP, and MRP2 expression in humans and nonhuman primate species. By measuring the plasma RIF concentration, we have clearly shown that RIF stimulates its own clearance via induction of the metabolic enzyme (and transporter).…”
Section: Effects Of Rif On Oatp1b1 Gene Expression In the Liver Smalmentioning
confidence: 94%
“…Drug interactions may reduce drug metabolizing enzyme and transporter activities through inhibition or may increase their activities through induction. Induction of enzymes and transporters can, in clinical practice, lead to reduced absorption and enhanced clearance of the drug itself and/or of a coadministered drug, thereby resulting in decreased drug exposure and loss of therapeutic efficacy (Chu et al, 2009, Turk et al, 2019. Compared to drug metabolizing JPET-AR-2020-000139 enzymes, much less is known of the induction of drug transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Trimethoprim DD(G)I modeling was performed with three different victim drugs (metformin, repaglinide, and pioglitazone) and one perpetrator drug (rifampicin). The parameters of the previously-developed PBPK models of metformin [ 20 ], repaglinide, pioglitazone [ 21 ], and rifampicin [ 22 ] that were applied for DDI modeling are reproduced in Tables S8, S11, S14 and S17 and DDI model processes are illustrated in Figures S14, S18, S21 and S25 of the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…To predict the published trimethoprim DDGI studies with metformin ( SLC22A2 808G>T , increased metformin transport) and pioglitazone ( CYP2C8*3 , increased pioglitazone metabolism), the trimethoprim model was applied with previously-built and evaluated DGI models of metformin and pioglitazone [ 20 , 21 ]. For the competitive inhibition of the variant OCT2 or CYP2C8 isoforms by trimethoprim, the same K i values as for the wildtype transporter or enzyme were applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation